Analysis of the factors influencing development of urinary tract infections in patients with spinal cord injuriеs - Sekulić, Aleksandra; Karadzov Nikolic, Aleksandra; Bukumiric, Zoran; Trajkovic, Goran; Corac, Aleksandar; Jankovic, Slobodan; Milicevic, Sasa (Vojnosanitetski pregled, 2016)
Background/Aim. Urinary tract infections are still the most frequent complications in patients with spinal cord injury (SCI). The aim of this study was to analyze the factors influencing development of urinary tract infections during rehabilitation in patients with SCI. Methods. This retrospective case/control study including 540 patients with SCI which were rehabilitated in the Clinic for Rehabilitation “Dr Miroslav Zotović” between January 2000 and December 2009. We used patient files and other available medical documentation for obtaining information contained in this study, such as the manner of bladder emptying, the type of neurological disorder of the bladder, the neurological level and completeness of a lesion, the injury etiology, treatment method, secondary complications and associated injuries, kidney and bladder calculosis, age and sex.  Results. Out of the total number of patients included in the study, 152 (28.1%) were without urinary tract infections, whereas 388 (71.9%) had urinary tract infections. There were 389 (72%) male and 151 (28%) female patients. The average age of patients without urinary tract infections was 51.0 ± 15.4 years, whereas the mean age of patients with urinary tract infections was 44.3 ± 16.9 years. The results of our study showed that the occurrence of urinary tract infections during rehabilitation in patients with SCIs was associated with the following factors: combined injuries (OR = 3.5), anemia (OR = 5.67), type of the bladder functional disorder (OR = 40–60) and crystals in urine (OR = 7.54). Conclusion. The physicians should take precautions and try to make the early diagnosis and rapid appropriate treatment of urinary tract infections in patients with SCI who also have functional bladder disorder, combined spinal injuries, anemia or urine crystals. Key words:spinal cord injuries; urinary tract infections; risk factors; urinary catheterization; multiple trauma; anemia; rehabilitation.
Keywords: Urinary Tract; Prediction; Urinary Tract Infections; Spinal cord injury